Potencialidades e limites de uma disciplina do curso de Educação Musical a distância na UFSCar - Carvalho, Isamara Alves (Universidade Federal de São Carlos, 2010)
This work was developed from issues and concerns related to the nature of human, musical and technological learning within a practical discipline of the Musical Education Bachelor Course (online education modality) of the Open University of Brazil at the Federal University of São Carlos (UAB / UFSCar). What educational processes are evidenced in a practical discipline of the course of online music education? What aspects could help build the online musical education teaching knowledge base? The theoretical fundaments permeated concepts of Online Education [Moore & Kearsley (2007), Moran (2006), Silva (2006)], pedagogical and musical Multidimensionality [Kramer (2000), Del Ben (2003), Hentschke (2001)], Pedagogical knowledge base and Teaching Knowledge [Shulman (1987), Tardif (2002) and Mizukami (2002)] among others. Data were collected in the virtual environment of the discipline as well as from the audiovisual records of the activities realized during face meetings. Are fellow volunteers in this research the virtual tutor, the students, as well as the teacher-researcher, author of this thesis. It was highlighted the learning related to groups coexistence representations, solidarity, the building of social bonding, conflict resolution within the data set on human relations in interactions in the network of computers connected to the Internet. Amongst specific learning aspects, regarding music, music education and the use of technology, it was possible to observe the diversity of challenges and achievements in the understanding and performing of musical pieces with the recorder, body percussion and alternative materials, and registering diversity in the use of audiovisual resources. I concluded that the modality of online education in this discipline has offered many dialogic, musical and technological challenges to the participants; however, it has not limited anyone to work in the search for fulfillment of the discipline goals. The limits and potentials are the choices and referrals attributes of the managers and the students of the discipline. It is possible to find out in this study the understanding and overcoming movement of conceivable limits, although not definitive. Other papers may discuss the significant learning starting from the speeches of the students themselves and participant tutor, besides analyzing other methodological possibilities in forwarding the same discipline in this online educational modality.
Keywords: Educação musical; Ensino a distância; Interação; Comunidade virtual; Aprendizagem; Online musical education; Interaction; Learning virtual communities; CIENCIAS HUMANAS::EDUCACAO